An Analysis of the Construction Approaches of Effective English Class in Junior Middle School Based on the Background of the New Curriculum Reform - Guo , Xiyun (Journal of Theory and Practice of Contemporary Education, 2023)
With the deepening reform of the education system and the innovation and optimization of the talent training model, we should pay more attention to junior high school English teaching, adopt targeted strategies to improve the timeliness of curriculum teaching, and then improve students' comprehensive application ability of English and strengthen professional literacy. Based on this, this paper, based on the background of the new curriculum reform, carries out in-depth exploration around the construction of efficient English classes in junior high school, aiming to provide valuable reference for the field of education and teaching. Building an efficient English classroom in junior high school is of great significance for improving students' professional performance and strengthening their comprehensive cultural quality. In order to improve the timeliness of English guest classroom teaching, teachers should adhere to the basic idea of teaching students according to their aptitude, reasonably apply targeted teaching methods according to the collective professional basic level, break through the shackles of traditional teaching models, take students as the main body of the classroom, create a good learning atmosphere, and promote the development of education and teaching.